Likovna dejavnost na oddelku za psihiatrično hitro pomoč - Mišica, Murka (Obzornik zdravstvene nege, 1981)
The emergency psychiatric unit functioning within the Centre for Mental Health is an open unit admitting non-psychotic patients in need of a brief medical and social management. Various forms of patient group therapy are described. With introduction of graphic arts the patients were offered new possibilities of expressing themselves through drawing and sculpture. The development of these activities will greatly contribute to identification of patients’ problems and planning of therapy. The author describes in detail various painting and drawing techniques, clay molding, tapestry weaving and the way of experiencing and evaluating these products.